2015
DOI: 10.1007/s00376-014-4127-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in regional heavy rainfall events in China during 1961–2012

Abstract: A new technique for identifying regional climate events, the Objective Identification Technique for Regional Extreme Events (OITREE), was applied to investigate the characteristics of regional heavy rainfall events in China during the period 1961-2012. In total, 373 regional heavy rainfall events (RHREs) were identified during the past 52 years. The East Asian summer monsoon (EASM) had an important influence on the annual variations of China's RHRE activities, with a significant relationship between the intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…The method has some distinctive features: (1) it considers both spatial and temporal continuities of regional events; (2) it is an index system with five single indices; an integrated index was established to characterize the features of regional events; (3) it is relatively objective with some adjustable parameters and is more convenient for application. The OITREE method had been applied to the regional high temperature ), the regional low temperature , and heavy rain events (Zou and Ren, 2015) and performed well in identifying these regional events. In this paper, the improved weighted average of precipitation (IWAP) index was used to study the variations of RDEs in southern China and achieved better results.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method has some distinctive features: (1) it considers both spatial and temporal continuities of regional events; (2) it is an index system with five single indices; an integrated index was established to characterize the features of regional events; (3) it is relatively objective with some adjustable parameters and is more convenient for application. The OITREE method had been applied to the regional high temperature ), the regional low temperature , and heavy rain events (Zou and Ren, 2015) and performed well in identifying these regional events. In this paper, the improved weighted average of precipitation (IWAP) index was used to study the variations of RDEs in southern China and achieved better results.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Ren et al . () also proposed an objective identification technique for regional extreme events (OITREE) and applied it to regional weather and climate events such as regional high and low temperature events (Gong et al ., ; Wang et al ., ), drought (Li et al ., ) and heavy rain (Zou and Ren, ) events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested above, the middle and lower YRB has experienced more frequent extreme precipitation events during 1960–2012. Not coincidentally, a regional precipitation extremes identify procedure OITREE (Objective Identification Technique for Regional Extreme Events) was applied recently to identify the RHREs (regional heavy rainfall events) in China during 1961–2012 (Zou and Ren, ). They reported that the East Asian summer monsoon (EASM) showed a significantly influence on precipitation extremes, especially for the middle and lower reaches of the Yangtze River and the northern part of South China.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of intense rainfall events (IREs) is being widely discussed in the whole globe because the consequences of such phenomena are the main responsible for human losses related to natural hazards as well as for countless socioeconomic losses, particularly in urban areas (Kobiyama et al ., ; Marengo et al ., ). Furthermore, several recent studies have estimated an increase in the recurrence and IREs worldwide (Allan and Soden, ; Zwiers et al ., ; Oliveira et al ., ; Zou and Ren, ; Niyogi et al ., ). In this context, part of the scientific community attributes the observed changes in the frequency of rainfall to anthropic activities, such as the increase of greenhouse gases emissions, land use and land cover changes and the intensification of the urbanization process (Meehl et al ., ; Pielke, ; Schroeder et al ., ; Rodell et al ., ).…”
Section: Introductionmentioning
confidence: 98%